DNA Methylation Correlates With Responses of Experimental Hydrocotyle vulgaris Populations to Different Flood Regimes - Wang, Mo-Zhu; Li, Hong-Li; Tang, Min; Yu, Fei-Hai (Frontiers in Plant Science, 2022)
Epigenetic mechanisms such as DNA methylation are considered as an important pathway responsible for phenotypic responses and rapid acclimation of plants to different environments. To search for empirical evidence that DNA methylation is implicated in stress-responses of non-model species, we exposed genetically-uniform, experimental populations of the wetland clonal plant Hydrocotyle vulgaris to two manipulated flood regimes, i.e. semi-submergence vs. submergence, measured phenotypic traits, and quantified different types of DNA methylation using MSAP (methylation-sensitive amplified polymorphism). We found different epi-phenotypes and significant epigenetic differentiation between semi-submerged and submerged populations. Compared to subepiloci (denoting DNA methylation conditions) for the CG-methylated state, unmethylation and CHG-hemimethylation subepiloci types contribute more prominently to the epigenetic structure of experimental populations. Moreover, we detected some epimarker outliers potentially facilitate population divergence between two flood regimes. Some phenotypic variation was associated with flood-induced DNA methylation variation through different types of subepiloci. Our study provides the indication that DNA methylation might be involved in plant responses to environmental variation without altering DNA sequences.